2003
DOI: 10.1128/aem.69.4.2349-2355.2003
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Mycobacterial Dehalogenase Rv2579 by Cumulative Mutagenesis of Haloalkane Dehalogenase LinB

Abstract: The homology model of protein Rv2579 from Mycobacterium tuberculosis H37Rv was compared with the crystal structure of haloalkane dehalogenase LinB from Sphingomonas paucimobilis UT26, and this analysis revealed that 6 of 19 amino acid residues which form an active site and entrance tunnel are different in LinB and Rv2579. To characterize the effect of replacement of these six amino acid residues, mutations were introduced cumulatively into the six amino acid residues of LinB. The sixfold mutant, which was supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
(31 reference statements)
0
16
0
Order By: Relevance
“…Currently, Mycobacterium is the only known genus expressing two such different enzymes within a single species. Comparison of the kinetic constants of wild-type DmbA with the previously constructed sixfold mutant LinB validated the earlier proposal of the catalytic function of this protein established from computer modeling and site-directed mutagenesis (32). Cloned genes could be used for DNA shuffling studies to reconstruct novel catalysts for degradation of important environmental pollutants, e.g., 1,2-dichloroethane and 1,2,3-trichloropropane, which was not possible previously due to the low homology of available dehalogenase genes.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Currently, Mycobacterium is the only known genus expressing two such different enzymes within a single species. Comparison of the kinetic constants of wild-type DmbA with the previously constructed sixfold mutant LinB validated the earlier proposal of the catalytic function of this protein established from computer modeling and site-directed mutagenesis (32). Cloned genes could be used for DNA shuffling studies to reconstruct novel catalysts for degradation of important environmental pollutants, e.g., 1,2-dichloroethane and 1,2,3-trichloropropane, which was not possible previously due to the low homology of available dehalogenase genes.…”
Section: Discussionmentioning
confidence: 74%
“…The specific activity of DmbA under optimal conditions is 0. (32). In the present study, the pure DmbA was obtained and its dehalogenase activity was confirmed.…”
Section: Figmentioning
confidence: 91%
See 2 more Smart Citations
“…Comparison of the kinetic mechanisms of DhlA, DhaA, and LinB showed that the overall reaction mechanisms are similar but that the rate-limiting steps differ, i.e., halide release in the case of DhlA (44), liberation of an alcohol in the case of DhaA (4), and hydrolysis of an alkyl-enzyme intermediate in the case of LinB (41). Partial improvement in the catalytic properties and modification of the substrate specificities of haloalkane dehalogenases by rational design (5,34) and directed evolution approaches (3,40) have recently been reported. However, it remains difficult to construct mutant enzymes with entirely new capabilities using only protein-engineering techniques, and therefore, the isolation of new family members is still desirable.…”
mentioning
confidence: 99%